PERINGKAT KINERJA KEUANGAN PADA PERUSAHAAN GO PUBLIK INDUSTRI MANUFAKTUR YANG TERCATAT PADA BURSA EFEK INDONESIA DENGAN MENGGUNAKAN Z-SCORE ALTMAN MODEL PERIODE 2010-2012 - Christian Hendrawardhana; Henrycus Winarto; Bambang Budiarto (Jurnal Ekonomi dan Bisnis, 2013)
Indonesia is a country that includes emerging markets and focused on the manufacturing sector. In the manufacturing sector will require funds on production activities, and these funds can be obtained from the credit. Meanwhile in Indonesia, many credit activity conducted by commercial banks, which is closely linked to the credit of bad credit. Bad credit can occur due to 2 factors, factors debtor or creditor factors. The meaning of this factor is negligence bank creditors in the debtor's credit analysis. But for manufacturing companies go public, they can raise funds in addition to the credit of the fund shares, many people who say that companies going public is a healthy company because it has passed various tests. Seeing this, the researchers would like to examine the statement and credit analysis test using the Z-Score models Atlman on manufacturing companies going public in Indonesia. The findings of this study indicate that the Z-Score Atlman models can be used for credit analysis in determining whether or not a company bankrupt.